The Maud Belt (East Antarctica) as an accretionary orogen in Rodinia: Isotopic composition, evolution and spatial variation - Wang, Cheng-Cheng; Jacobs, Joachim; Marschall, Horst R.; Hemming, Sidney; Jacques, Guillaume; Läufer, Andreas (Gondwana Research, 2025)
The Maud Belt of East Antarctica represents a late Mesoproterozoic orogen along the periphery of the Proto-Kalahari Craton, and a better understanding of its orogenic nature helps to elucidate the configuration of Kalahari within the Rodinia supercontinent. In this study, we present original and compiled zircon U–Pb geochronological and Hf isotopic data spanning ca. 1180 to 950 Ma along with whole-rock Nd isotopes, covering a broad expanse of the Maud Belt and the adjacent Archean Grunehogna Craton, in an attempt to delineate the spatial and temporal patterns of isotopic compositions and evolution, and to better understand the orogenic architecture and style. Spatial isotopic variations are particularly evident in the western front of the orogen (western H.U. Sverdrupfjella) in contrast to other regions. The former exhibits a wide range of isotopic compositions, with the majority showing highly evolved signatures, indicating that the orogenic crust developed through the reworking of pre-existing Archean–Paleoproterozoic continental crust. In contrast, most other regions of the Maud Belt are characterized by relatively juvenile Hf and Nd isotopic compositions, which are interpreted to be derived from a mixture of juvenile magmas and Paleoproterozoic crust. The Hf isotopic evolution from 1180 Ma to 950 Ma indicates significantly less reworking of pre-existing continental crust compared to other contemporaneous Rodinia-forming orogens, including the Grenville Orogen itself, and emphasizes a predominant addition of juvenile material, implying a continuous subduction process. The isotopic investigation in this study, combined with the geological and paleomagnetic evidence, indicates that the Maud Belt most likely represents an exterior accretionary orogen along the eastern margin of the Proto-Kalahari Craton, rather than being part of the continental collision zones that led to Rodinia amalgamation.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi; paleogeografi; paleomagnetisme

Neoproterozoic geodynamic evolution of easternmost Kalahari: Constraints from U-Pb-Hf-O zircon, Sm-Nd isotope and geochemical data from the Schirmacher Oasis, East Antarctica - Jacobs, Joachim; Mikhalsky, Evgeny; Henjes-Kunst, Friedhelm; Läufer, Andreas; Thomas, Robert J; Elburg, Marlina; Wang, Chengcheng; Estrada, Solveig; Skublov, S G (Precambrian Research, 2020)
Late Tonian (ca. 785–760 Ma) granodioritic to granitic orthogneisses of the Schirmacher Oasis region in Dronning Maud Land (DML), East Antarctica, are interpreted as recording an active continental margin setting at the periphery of Kalahari and Rodinia. The rocks probably represent exposures of a significant tectonic province hidden beneath the ice, the erosional remnants of which are recorded as detrital zircons in late Tonian-Cryogenian metasedimentary rocks throughout central and eastern DML, as well as in ice-rafted debris from recent sediments offshore Dronning Maud Land. The orthogneisses have single-stage Sm-Nd model ages of ca. 1.3–1.5 Ga and zircon Hf-signatures (εHft = +2 – +5), indistinguishable from the adjacent Grenville-age basement rocks of easternmost Kalahari. Their geochemistry suggests that they evolved in the late stages of a continental margin magmatic arc and possibly within a roll-back tectonic framework, suggestive of subduction of relatively old oceanic lithosphere. The eastern Kalahari continental arc is one of a number of continental arcs that characterize the western part of the fragmenting Rodinia and document the supercontinent “turning inside out” after its formation at ca. 1000 Ma and a period of relative tectonic quiescence between ca. 900 and 800 Ma. The rocks show an ultra-high temperature metamorphic overprint that was accompanied by syn-tectonic magmatism from ca. 650 to 600 Ma. The high temperature metamorphism is interpreted to relate to back-arc extension that also led to major anorthosite magmatism elsewhere, prior to continental collision in the region. The rocks lack the subsequent widespread high-grade metamorphic overprint at ca. 590–500 Ma which occurs in the adjacent regions due to Himalayan-style continental collision along the East African-Antarctic Orogen during Gondwana assembly.
Keywords: Dronning Maud Land; geokronologi; geologi

Late Neoproterozoic–Cambrian magmatism in Dronning Maud Land (East Antarctica): U–Pb zircon geochronology, isotope geochemistry and implications for Gondwana assembly - Wang, Cheng-Cheng; Jacobs, Joachim; Elburg, Marlina A.; Läufer, Andreas; Elvevold, Synnøve (Precambrian Research, 2020)
Dronning Maud Land (DML) is a key area for the better understanding of the geotectonic history and amalgamation processes of the southern part of Gondwana. Here, we present comprehensive new zircon U–Pb–Hf–O, whole-rock Sm–Nd isotopic and geochemical data for late Neoproterozoic-Cambrian igneous rocks along a profile from central to eastern DML, which provides new insights into the crustal evolution and tectonics of the region. In central DML, magmatism dominantly occurred at 530–485 Ma, with 650–600 Ma charnockite and anorthosite locally distributed at its eastern periphery. In contrast, eastern DML experienced long-term and continuous granitic magmatism from ca. 650 Ma to 500 Ma. In central DML, the 650–600 Ma samples are characterized by highly elevated δ18O (7.5–9.5‰) associated with slightly negative to positive εHf(t) values (−1 to +3), indicating significant addition of high-δ18O crustal components, such as sedimentary material at the margin of the Kalahari Craton. Evolved Hf isotopic signatures (εHf(t) = −15 to −6) and moderately elevated O isotopic data (δ18O = 6–8‰) of the Cambrian granitic rocks from central DML indicate a significant incorporation of the pre-existing, old continental crust. In eastern DML, the suprachondritic Hf–Nd isotope signatures and moderate δ18O values of the late Neoproterozoic granites (650–550 Ma) from the Sør Rondane Mountains support the view that they mainly originated from crust of the Tonian Oceanic Arc Super Terrane (TOAST). The post-540 Ma granites, however, have more evolved Hf and Nd isotopic compositions, suggesting an increasing involvement of older continental components during Cambrian magmatism. Nd isotopes of the Cambrian granitic rocks in DML display an increasingly more radiogenic composition towards the east with model ages ranging from late Archean to Mesoproterozoic times, which is in line with the isotopic trend of the Precambrian basement in this region. The late Neoproterozoic (>600 Ma) igneous rocks in central and eastern DML were emplaced in two independent subduction systems, at the periphery of the eastern Kalahari Craton and somewhere within the Mozambique Ocean respectively. The accretion and assembly of the TOAST to the eastern margin of the Kalahari Craton and their collision with surrounding continental blocks was followed by extensive post-collisional magmatism due to delamination tectonics and orogenic collapse in the Cambrian. The late Neoproterozoic–Cambrian igneous rocks in DML thus record an orogenic cycle from subduction-accretion, continental collision to post-collisional process during and after the assembly of Gondwana.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi